2001
DOI: 10.1097/00000539-200105000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intranasal Fentanyl on the Emergence Characteristics After Sevoflurane Anesthesia in Children Undergoing Surgery for Bilateral Myringotomy Tube Placement

Abstract: We examined the use of nasally administered fentanyl for the relief of agitation or discomfort after placement of bilateral myringotomy tubes in 150 children ages 6 mo to 5 yr using a prospective, double-blinded design. Fentanyl 2 microg/kg was found to reduce the incidence of agitation in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 15 publications
1
98
4
Order By: Relevance
“…In pediatric anesthesia, fentanyl is commonly used for analgesia and for reducing agitation; in several studies, the preemptive analgesic approach such as intravenous (IV) fentanyl 2.5 μg/mL or intranasal fentanyl 2.0 μg/mL successfully reduced emergence agitation [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In pediatric anesthesia, fentanyl is commonly used for analgesia and for reducing agitation; in several studies, the preemptive analgesic approach such as intravenous (IV) fentanyl 2.5 μg/mL or intranasal fentanyl 2.0 μg/mL successfully reduced emergence agitation [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have shown that intraoperative use of analgesics or regional blocks decrease the incidence of PAA in children, [10][11][12] demonstrating the relationship between pain and agitation in children. Other studies have demonstrated a significant incidence of PAA despite adequate analgesia 1,13 or after painless procedures such as magnetic resonance imaging (MRI), 4 suggesting a possible anesthetic-related etiology for this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al, found that intraoperative remifentanil decreased the incidence of ED in children undergoing adenotonsillectomy [60]. Fentanyl, given either IV 2.5 μg/kg or intranasally 2 μg/kg during moderately painful surgery, has also been shown to decrease emergence agitation in children [61][62][63][64]. Bong et al, confirmed the preventative effects of fentanyl and further identified a lack of fentanyl as an independent risk factor for ED [34].…”
Section: Nsaids and Opioidsmentioning
confidence: 99%